The Use of Beneficial Microbes Tolerant of the Pyraclostrobin Fungicide, in Controlling the Pathogen Colletotrichum, the Cause of Anthracnose Disease in Chili Plants - Tubagus, Satria Wahyu; Syib’li, Muhammad Akhid; Abadi, Abdul Latief (Research Journal of Life Science, 2023)
Global production of chilies is significantly influenced by various biotic and abiotic factors. anthracnose is likely the main inhibiting factor reducing chili productivity in various countries. The use chemicals still formed the basis of disease control. Trichoderma sp. and FB1 bacterial is one such tolerant beneficial microbe belonging to the fungus and bacteria group that can survive under chemical pressure and exhibit antagonistic effects against the pathogen Colletotrichum sp. by the in vitro assay, it was found that in the antagonistic of Colletotrichum sp. with bacteria FB1 and Trichoderma sp., there was a significant difference, that the growth of Colletotrichum sp. could be inhibited by 69%. In the compatibility assay of bacteria FB1 and Trichoderma sp., no significant antagonistic response was found from both beneficial microbes. In the fungicide tolerance test of all isolates, it was found that beneficial microbes could still grow on growth media with a mixture of pyraclostrobin fungicide at a dose of 0.25 ul/ml. FTIR analysis showed the functional groups of the secondary metabolites of both the antagonistic bacteria and the antagonistic fungi had very high similarity in O-H and C=O groups. However, further research is needed on the mechanism of the secondary metabolites of the beneficial microbes involved in the inhibition of the pathogen Colletotrichum sp.